Stability and Coulomb fission of multiply charged molecular clusters - Harris, Christopher (2015)
The stability of multiply charged clusters under the influence of electrostatic repulsion contained within them is determined by the balance between the cohesive forces holding the cluster together and the repulsion between the charges. Experimentally, the onset of stability is determined through the observation of a critical size, below which the cluster ceases to be observed. There is a region above the critical size in which a multiply charged cluster becomes metastable and the fragmentation into charged fragments can be detected in the experimental time frame. The most interesting pathway is the separation of the precursor into charged fragments which is termed Coulomb fission, which if the metastable peaks from the processes are observed, can contain information about the interactions between thecharged dielectric fragments and add to our understanding of how like charged species interact in nature. The work contained presents an investigation of the multiply charged molecular cluster systems: (C6H6)nz+, (CH3CN)n Z+, (C4H8O)n z+, (NH3)n z+ and (H2O)n z+. Using updated experimental procedures, the critical sizes for multiply charged molecular clusters is determined for charge states of up to z = 8+ and are compared to predictions made with existing theories. The coulomb fission into charged fragments is observed using the mass analysed kinetic energy (MIKE) scanning technique and by simulating the shape of the experimental peak, the experimental energy release following the separation is determined. This energy is found to agree well with the predictions of a dielectric particle drop model which describes the interactions between dielectric bodies.